2009
DOI: 10.1016/j.polymer.2009.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of highly hydrophilic polyurethane based on diisocyanate with ether group

Abstract: Highly hydropihilic polyurethane elastomers (PUEs) were synthesized from 1,2-bis(isocyanate) ethoxyethane (TEGDI), poly(ethylene oxide-co-propylene oxide) copolyol (EOPO) and 1,4-butane diol/1,1,1-trimethylol propane (75/25)(wt/wt) by a prepolymer method. 4,4'-diphenylmethane diisocyanate (MDI)-based PUEs were synthesized as a control as well. Fourier-transform infrared spectroscopy (FT-IR) and differential scanning calorimetry (DSC) measurement revealed that the degree of microphase separation of the TEGDI-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…However, when the concentration of inulin in the reaction is close to 66% (sample PU-INU66, Figure 6b), it is obtained a hydrophobic polyurethane due to the cross-linking caused by a higher concentration of non-bonded inulin (free inulin), within the structure of the polyurethane material PU-INU66. For the samples with relatively low inulin content (PU-INU33 and PU-INU50) it is observed that both have a similar mechanic and thermic properties compared to a hydrophilic polyurethane synthesized with PCL-diol or even as a polyurethane-based on diisocyanate with ether group such as poly(oxyethylene) glycol [49], this due to the presence of inulin chains. These polyurethane materials can uptake water by hydrogen bonding since the molecule has available link sites in contrast with the sample with the highest inulin content (PU-INU66) which has less amount of available link sites due to the presence of more free inulin that could also hydrolyze and make the structure unstable [60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, when the concentration of inulin in the reaction is close to 66% (sample PU-INU66, Figure 6b), it is obtained a hydrophobic polyurethane due to the cross-linking caused by a higher concentration of non-bonded inulin (free inulin), within the structure of the polyurethane material PU-INU66. For the samples with relatively low inulin content (PU-INU33 and PU-INU50) it is observed that both have a similar mechanic and thermic properties compared to a hydrophilic polyurethane synthesized with PCL-diol or even as a polyurethane-based on diisocyanate with ether group such as poly(oxyethylene) glycol [49], this due to the presence of inulin chains. These polyurethane materials can uptake water by hydrogen bonding since the molecule has available link sites in contrast with the sample with the highest inulin content (PU-INU66) which has less amount of available link sites due to the presence of more free inulin that could also hydrolyze and make the structure unstable [60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 97%
“…The results for the PU-INU degradation under specific pH and temperature conditions could be The hydrophobic/hydrophilic character of polyurethanes depends on its chemical structure and especially on the nature of physical and chemical interactions between urethane moieties from polar hard segments and polyol soft segments, where hydrogen bonds are predominant [45][46][47][48][49]. Therefore, it was expected that PU-INUs will exhibit hydrophilic properties, like when a hydrophilic chain extender is incorporated into the synthesis.…”
Section: Degradability Assessment Of Pu-inumentioning
confidence: 99%
“…As such, this type of PEU can be used as biomaterials, filter membranes, biosensors, water permeable materials, etc. [5], [6].…”
Section: Surface Properties Of the Pu Materialsmentioning
confidence: 99%
“…Generally, the wettability of a solid surface is mainly caused by the chemical composition and structure asperities, which depend on surface energy and geometric structure [7]. To obtain hydrophobic polymer surfaces, coating with low surface energy materials such as fluoroalkylsilane can be helpful [8][9][10][11][12]. On the other hand, geometric structures including rough structures and regular micro/nano patterns are also crucial [13,14].…”
Section: Introductionmentioning
confidence: 99%